Ethnic differences in association of outcomes with trimethylamine N‐oxide in acute heart failure patients. (29th June 2020) - Yazaki, Yoshiyuki; Aizawa, Kenichi; Israr, Muhammad Zubair; Negishi, Keita; Salzano, Andrea; Saitoh, Yuka; Kimura, Natsuka; Kono, Ken; Heaney, Liam; Cassambai, Shabana; Bernieh, Dennis; Lai, Florence; et al.
Abstract: Aims: The aim of this study was to investigate whether ethnicity influences the associations between trimethylamine N‐oxide (TMAO) levels and heart failure (HF) outcomes. Methods and results: Trimethylamine N‐oxide levels were measured in two cohorts with acute HF at two sites. The UK Leicester cohort consisted mainly of Caucasian ( n  = 842, 77%) and South Asian ( n  = 129, 12%) patients, whereas patients in the Japanese cohort ( n  = 116, 11%) were all Japanese. The primary endpoint was the measurement of all‐cause mortality and/or HF rehospitalization within 1 year post‐admission. Association of TMAO levels with outcome was compared in the entire population and between ethnic groups after adjustment for clinical parameters. TMAO levels were significantly higher in Japanese patients [median (interquartile range): 9.9 μM (5.2–22.8)] than in Caucasian [5.9 μM (3.6–10.8)] and South Asian [4.5 μM (3.1–8.4)] ( P  < 0.001) patients. There were no differences in the rate of mortality and/or HF rehospitalization between the ethnic groups ( P  = 0.096). Overall, higher TMAO levels showed associations with mortality and/or rehospitalization after adjustment for confounders ( P  = 0.002). Despite no differences between ethnicity and association with mortality/HF after adjustment ( P  = 0.311), only in Caucasian patients were TMAO levels able to stratify for a mortality/HF event ( P  < 0.001). Conclusions: Differences were observed in the association of mortality and/or rehospitalization based on circulating TMAO levels. Elevated TMAO levels in Caucasian patients showed increased association with adverse outcomes, but not in non‐Caucasian patients.